Hubungan Tingkat Pengetahuan Tentang Diet Diabetes Melitus Dengan Komplikasi Gagal Ginjal Kronik - Refianti - Marsinta; Yesi - Hasneli; Ari Pristiana Dewi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
Renal insufficiency due to diabetes disease has subsequently been known by the name of Diabetic Kidney Disease (DKD) or Diabetic Nephropathy (ND) is a complication of diabetes that is included in microvascular complications, the complications that occur in small blood vessels (small). The purpose of this research was to determined the level of knowledge about DM dietery with complication of  kidney failure. Samples of this research taken by using purposive sampling technique. This study used a” descriptive – correlation” research design with cross sectional study " . Total sample of 74 people with using purposive sampling technique sampling by taking into account the inclusion criteria Measuring instrument  to look at the diet by using kuesioner knowledge and to see the complications of chronic renal failure was using secondary data . The analysis used univariate and bivariate analysis with the chi-square test . The results showed a high knowledge of the results of as many as 42 ( 56.8 % ) and low knowledge of as many as 32 (43.2 %), while the average stage of CRF in stage IV were 12 respondents ( 16.2 % ) and stage V as 62 respondents ( 83.8 % ). The results of this study with p value = 0,843, There is no relationship between the level of knowledge about the diet of patients with DM with complications of chronic renal failure. The results of this study are expected to be one of the nursing interventions to improve diabetes patients knowledge about the diet of diabetic nephropathy in order not to aggravate the situation. Keywords: Complications, Diabetes Mellitus, diet, Kidney Failure